‘It hasn’t Been the Best Year, but here I am’: Young Adults Interpreting their Agency in Relation to the Self-Governing Discourse, Social Relations and Life Contexts - Niemi Anna-Maija (Springer, 2022)
The aim of this article is to explore with a longitudinal research approach how young adults narrate their life course and build their agency in relation to societal expectations with the support of their social relations and societal awareness. The article leans on the ethnography-based life historical interview data produced in 2017–2020 with a small group of Finnish young adults who are regarded as having a migrant or special education background. The discursive–narrative analysis shows that the interviewees make sense of themselves and their agency within the individualised self-governing discourse, especially when narrating the future. They also, however, distance themselves from that discourse by attaching themselves to social and religious relations and societal inequalities, especially when narrating the present and the past. Based on the analysis, I claim that recognising their own position in the school system and in wider society helped the interviewees understand obstacles along the way and be understanding towards themselves and others.